Analyzing the Role of Job Satisfaction and Commitment to Employees' OCB - G. Andreopoulos; Eva Andriani; Muhammad As'ad Mubarok Al Jauhari; Iswahyu Pranawukir; Rifaldi (PT Inovasi Pratama Internasional, 2023)
OCB or organizational citizenship behavior is a behavior of employees who voluntarily perform jobs that are outside the job desk or standard tasks that are usually performed and assigned to them. Usually this is done in order to help the company survive in achieving their goals. The study aims to review and also learn about the influence of organizational culture and also job satisfaction as well as organizational commitment of employees to organizational citizenship behavior . The research itself was conducted at XYZ Corporation. The population sample used in this study was approximately 67 employees. This research advances saturated sampling techniques as well as simple random samplings. Taking data yourself through the questionnaire. Meanwhile, the analytical technique used in this study is double linear regression. The results of the analysis showed that organizational culture and job satisfaction as well as organizational commitment have a very significant and positive influence on organizational citizenship behavior. The higher the organizational culture among the employees, the higher the OCB. In the same way, the higher the organizational commitment will then be compared to the OCB.